Keating construction dispute resolution handbook - Gaitskell, Robert (ICE Publishing, 2016)
'Keating Construction Dispute Resolution Handbook' provides straightforward and pragmatic advice on dealing with construction disputes, at all stages, using principles that are applicable internationally. It covers the complete spectrum of dispute resolution expertise required by construction professionals.